EFEKTIVITAS COOPERATIVE SCRIPT TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA PESERTA DIDIK KELAS IV SDN SAMPURNA 1 - Mahmudah; Ella; Agay Maarif; Nur Fajrina; Marlina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to improve learning outcomes in Pancasila Education through the application of the Cooperative Script learning model to fourth-grade students at SDN Sampurna 1. This study is a classroom action research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. There were 15 students participating in this study. Research data were collected through observation of teacher activities, observation of student activities, and learning outcome tests. Data analysis was conducted using quantitative and qualitative descriptive methods. The results showed that the application of the Cooperative Script model was able to improve teacher activities from the category of fairly good to very good, as well as improve student activities from the category of fairly active to very active. This increase in learning activity had an impact on student learning outcomes, as shown by an increase in learning completeness from 40% at the beginning to 86.67% in cycle II. Based on these results, it can be concluded that the Cooperative Script learning model is effective in improving the Pancasila Education learning outcomes of fifth-grade students at SDN Sampurna 1.